Maternal indicators of admission to high obstetric risk during a viral pandemic (Research, Society and Development, 2022)
The objective of this study was to identify whether the viral pandemic changed the maternal indicators of admission to high obstetric risk, describe the causes of obstetric hospitalizations and compare the relationship of indicators in a time frame before and after a viral pandemic. This is a cross-sectional, descriptive study, with a documentary character and a quantitative approach, referring to the period of six months prior to the installation of the pandemic in Alagoas and the first six months thereafter, whose data analyzed were the indicators of hospitalization of a high-quality maternity hospital. risk. Of the 953 hospitalizations collected, about 49.84% took place between September 2019 and February 2020, and 50.16% between March and August 2020, the time that corresponds to the beginning of the pandemic. It was observed the prevalence of the same indicators, occupying the first and second place in both moments of the research. On the other hand, although to a lesser extent, some indicators showed oscillations. The data from this research revealed that the number of high-risk pregnancies is still high and the arrival of the viral pandemic has slightly modified maternal indicators, as some showed an increase and others a decrease.